ChildProgramming-C: as an improvement of the collaborative dimension of the ChildProgramming model (2018)
In order to design reusable processes by structuring and designing activities for teams of people through Collaboration Engineering, the Research and Development Group in Software Engineering (IDIS) of the University of Cauca, has proposed the model ChildProgramming-C, which seeks to make a contribution from the Collaborative Engineering approach to the ChildProgramming Software development model. In the progress of the investigation two exploratory case studies have been carried out with children of an Educational institution, where it was evidenced that in spite of theoretically proposing collaborative activities for children to learn to develop software, during practice there are situations that do not guarantee positive interdependence, individual responsibility and equal participation, as fundamental characteristics of collaborative work. Therefore, a preliminary phase is proposed to the Childprogramming model, which seeks to sensitize children about the importance of collaboration by being part of a team, through ludic strategies, allowing the development of social, cognitive and computational thinking skills. This article shows the experience of the sensitization phase and the evaluation through the application of a confi rmatory case study.